La importancia de la cadena de valor en los agronegocios en la provincia de el oro - Quevedo Alberca, Robert Andres (Machala : Universidad Técnica de Machala, 2021)
The development of the Ecuadorian agricultural field has been destined to the production of foodstuffs that are part of the basic food basket and have been a source of employment generation and dynamism of the mixed economy. The objective of this research is to analyze and understand the importance of the agribusiness value chain in the province of El Oro. The importance of the agribusiness value chain contributes to and improves income distribution in rural areas, facilitates market insertion, reduces transaction costs, increases the exchange of local information, and improves the transfer of ICTs. El Oro in its different productive links concentrates four economic axes, which are distributed by small, medium and large companies; its economic activities are centered on Commerce, Agriculture, Livestock and Fishing, Manufacturing and Mining. It is concluded that 85% of its production is agricultural products, distributed among small, medium and large farmers that generate employment and development in the fourteen cantons of the province.
El desarrollo del campo agrícola ecuatoriano se ha destinado a las producciones de alimentos que se ubican en la canasta básica y que han sido fuente de generación de empleo y dinamismo de la economía mixta. La presente investigación tiene como objetivo analizar y conocer la importancia de la cadena de valor de los Agronegocios en la Provincia de El Oro. La cadena de valor ayuda contribuir y mejorar la distribución del ingreso en áreas rurales, facilitan la inserción al mercado, reducen los costos de transacción, aumentan el intercambio de información local, mejoran la transferencia de las TIC´s. El Oro en sus diferentes eslabones productivos concentra cuatros ejes económicos, que están distribuidos por pequeñas, medianas y grandes empresas; sus actividades económicas se centran el Comercio, Agricultura Ganadería y Pesca, Manufactura y Minería. Se concluye que el 85% de su producción son productos de origen agrícola, distribuidos entre pequeños, medianos y grandes agricultores que generan empleo y desarrollo en los catorce cantones de la Provincia.
Keywords: CADENA; VALOR; CRECIMIENTO; ECONÓMICO